INTERFERENSI BAHASA INDONESIA DALAM PENGGUNAAN BAHASA INGGRIS MAHASISWA EFL - Yustih Yasih; Dadang Ismatullah; Andi Muh. Ruum Sya'baan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study investigates the influence of the Indonesian language on English usage among students in an English Education Study Program at a state university in Indonesia. The research aims to identify and analyze the forms of linguistic interference from the students’ first language (L1) in their English production, both written and spoken. Employing a qualitative descriptive approach, data were collected through student essays, semi-structured interviews, and classroom observations. The data were analyzed using an error analysis framework based on Corder’s model, focusing on lexical, syntactic, morphological, and semantic errors. The findings reveal a consistent pattern of negative transfer, in which students directly translate Indonesian structures into English without considering structural and pragmatic differences. This study contributes to the field of second language acquisition by highlighting the persistence of L1 interference in EFL contexts and emphasizing the need for contrastive, context-based teaching strategies. It also provides practical implications for English instructors in designing more responsive learning environments.